EFFECT GIVING WHITE WOOD LEAVES (MELALEUCA LEUCADENDRA) THERAPY IN CHILD TODDLERS WITH ACUTE RESPIRATORY TRACT INFECTION DISORDERS AT PUSKESMAS TOROH 1 - Nurya Kumalasari; Laily Himawati; Vera Vrewulan Dari (Lppm Unan, 2023)
Background: Acute respiratory infection (ARI) is an acute infection involving the upper and lower respiratory tract organs. This infection is caused by viruses, fungi and bacteria. , Acute Respiratory Infection ARI is the cause of 15% of under-five deaths, which is estimated to be 922,000. While in Indonesia in 2017 there was an increase of 63.45% of the number of underfive deaths 0.16% higher than in 2014 which was only 0.08%. The incidence rate for toddlers exposed to ISPA in Central Java province is 3.6% (KEMENKES, 2017). Methodology : This type of quantitative research has an experimental research design and uses a quasi-experimental research design, one group preset and post test. The subjects in this study were toddlers aged 1 until 5 years. Results: The research results obtained were toddlers with problem respiratory system disorders, the mother said that her child had no runny nose and no nose discharge, no redness on the outside of the nose and a good appetite Conclusion: there is a decrease in respiratory disorders in toddlers after being given eucalyptus leaf steam therapy.